Understanding of cardiovascular disease among patients with hypercholesterolemia – a qualitative exploration - Samsudin, Suhaiza; Mohd Arifin, Siti Roshaidai; Md Aris, Mohd Aznan; Abdullah, Fa’iza (Academy of Family Physicians of Malaysia, 2019)
Background: The burden of cardiovascular disease is increasing rapidly in Malaysia but there are limited studies conducted on the understanding of cardiovascular disease among patient who have been identified as at risk of developing cardiovascular disease. Without such an understanding, an early detection and management of the cardiovascular disease within primary care setting would be challenging. Objectives: The objective of this study was to explore the understanding of cardiovascular disease among patients with hypercholesterolemia. Methods: A qualitative study design was used. Semi structured interviews were conducted at a Family Health Clinic in Kuantan, Pahang Darul Makmur from May to August 2018. Purposive sampling was applied to recruit 13 patients with total cholesterol level of more than 5.2 mmol/L and low density lipoprotein of more than 4.9mmol/L. Interviews were audio-recorded, transcribed verbatim and then subjected to interpretive thematic analysis using NVIVO 12 software. Results: Four themes emerged from the analysis: perceived causes of cardiovascular diseases, response and action, manifestation of heart disease and challenges in seeking medical care. Risk factors and typical presentation of heart disease were less recognizable. Personal hurdle, families and sociocultural factors were identified as the main barriers for uptake of health care services. Participants were heavily influenced by folk medicine to scale down their cholesterol level. Whilst the majority of the participants were unaware of their risk to develop cardiovascular disease, it appears that there was a lack of understanding on cardiovascular disease among the participants. Conclusion: This study clearly identified gaps and inaccuracies of cardiovascular disease understanding among participants with hypercholesterolemia. Patients at risk need to be educated about the disease through health education, counselling or community program.